2008
DOI: 10.3200/jrpl.142.4.395-412
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Self-Knowledge Scale: Correlations and Incremental Validity of a Cross-Cultural Measure Developed in Iran and the United States

Abstract: The authors used Iranian (N = 723) and American (N = 900) samples to develop an Integrative Self-Knowledge Scale for measuring a temporally integrated understanding of processes within the self. They administered this new instrument, the Mindfulness Scale (K. W. Brown & R. M. Ryan, 2003), the Reflective and Experiential Self-Knowledge Scales (N. Ghorbani, M. N. Bing, P. J. Watson, H. R. Davison, & D. L. Lebreton, 2003), and additional sample-specific measures to 3 separate groups of university students in each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
99
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 78 publications
(113 citation statements)
references
References 32 publications
7
99
0
2
Order By: Relevance
“…Islamic philosophy identifies self-knowledge and self-control as critical in personal efforts to achieve the Muslim moral ideal (Motahharī, 2000;Shimamoto, 2008), and measures of these psychological processes do indeed predict higher levels of adjustment and sincere religious commitments in Iran (e.g., Ghorbani, Watson, Rezazadeh, & Cunningham, 2011). In the present project, Iranian university students, therefore, responded to the Self-Control Scale (Tangney, Baumeister, & Boone, 2004) and to three measures assessing various aspects of self-knowledge: the Integrative Self-Knowledge (Ghorbani, Watson, & Hargis, 2008), Mindfulness (Brown & Ryan, 2003), and Reflection (Trapnell & Campbell, 1999) scales.…”
Section: Measures Of Psychological Adjustmentmentioning
confidence: 71%
See 1 more Smart Citation
“…Islamic philosophy identifies self-knowledge and self-control as critical in personal efforts to achieve the Muslim moral ideal (Motahharī, 2000;Shimamoto, 2008), and measures of these psychological processes do indeed predict higher levels of adjustment and sincere religious commitments in Iran (e.g., Ghorbani, Watson, Rezazadeh, & Cunningham, 2011). In the present project, Iranian university students, therefore, responded to the Self-Control Scale (Tangney, Baumeister, & Boone, 2004) and to three measures assessing various aspects of self-knowledge: the Integrative Self-Knowledge (Ghorbani, Watson, & Hargis, 2008), Mindfulness (Brown & Ryan, 2003), and Reflection (Trapnell & Campbell, 1999) scales.…”
Section: Measures Of Psychological Adjustmentmentioning
confidence: 71%
“…Development of a Persian Integrative Self-Knowledge Scale occurred during scale development procedures (Ghorbani et al, 2008). For all other measures, one individual translated the scale expressed in English into Persian, and then another translated the Persian back into English.…”
Section: Methodsmentioning
confidence: 99%
“…The basic idea is that self-insight combined with self-control should help purify the Muslim self and bring it into a closer connection with God, who according to the Qur'an is always closer to an individual than "his jugular vein" (50:16: (Ali 1993)). Studies using integrative self-knowledge (Ghorbani et al 2008) and self-control (Tangney et al 2004) scales have confirmed the relevance of this "perfect man" for understanding Iranian religious adjustment (Ghorbani et al 2011;Ghorbani et al 2016b). Weber, incidentally, also linked the Protestant work ethic with a "systematic self-control" (Weber [1920] 1996, p. 115) that required self-knowledge.…”
Section: Work Ethics In Iranmentioning
confidence: 99%
“…The integrative self-knowledge measure included 12 statements that reflected attempts of an individual to make sense out of past, present, and desired future self-experience (Ghorbani et al 2008; α = 0.75, M = 3.25, SD = 0.70). A representative item said, "If I need to, I can reflect about myself and clearly understand the feelings and attitudes behind my past behaviors.…”
Section: Integrative Self-knowledgementioning
confidence: 99%
“…In this study, Job Satisfaction Scale (Şahin and Durak, 1994), Emotion Regulation Scale (Gross and John, 2003), Toronto Mindfulness Scale (Toronto MS), (Lau et al, 2006), Integrative Self Knowledge Scale (Ghorbani, Watson and Hargis, 2008) and Personal Information Form were used. Ulaşan Özgüle (2011) adapted Emotion Regulation Scale to Tuskish Culture.…”
Section: Research Samplementioning
confidence: 99%